1986
DOI: 10.1007/bf02374336
|View full text |Cite
|
Sign up to set email alerts
|

Localization of aluminium in the leaves of some aluminium-accumulating species

Abstract: Summary Transverse sections of leaves of some aluminium-accumulating and nonaccumulating species of the cerrado vegetation of central Brazil were coloured using aluminon to identify the tissues where aluminium occurs or is deposited. None of the tissues of the nonaccumulating species showed evidence of high concentrations of A1. All of the aluminium accumulating species showed high concentrations of AI in all of the elements of the phloem of the midrib and the secondary veins and total absence of it in the ves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
2
12

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 4 publications
1
15
2
12
Order By: Relevance
“…Haridasan et al (1986) have reported similar Al-distribution in leaf cells of Al-accumulating species of the Brazilian 'Cerrado', but in contrast to our findings (Cuenca and Herrera, 1987) they did not report AI in the xylem vessels. Haridasan (1988) andHaridasan et al (1986) postulate a possible metabolic role for AI in this type of plants.…”
Section: Introductioncontrasting
confidence: 56%
“…Haridasan et al (1986) have reported similar Al-distribution in leaf cells of Al-accumulating species of the Brazilian 'Cerrado', but in contrast to our findings (Cuenca and Herrera, 1987) they did not report AI in the xylem vessels. Haridasan (1988) andHaridasan et al (1986) postulate a possible metabolic role for AI in this type of plants.…”
Section: Introductioncontrasting
confidence: 56%
“…No co-localization was seen with P or the other elements measured here, which is in line with reports on Al transport via the xylem as a complex bound to organic acids, such as citrate in tea plants (Morita et al 2004). More than 20 years ago, simple haematoxylin staining procedures had already shown the specific location of Al in the phloem tissue of Al-accumulating species from the Brazilian Cerrado region (Haridasan et al 1986). Here, this specific localization of Al in the phloem tissue is thus finally confirmed in the Al-accumulating tea plant using a sample preparation technique that avoids retranslocation of the elements during the sample preparation procedure.…”
Section: Resultsmentioning
confidence: 97%
“…Bases and P were present in low concentrations in the three sites and soils showed a high proportion of sand as had been reported for other sites of the region (Ramirez et al, 2007). Haridasan et al (1986) showed Al sequestration in the cell wall of Miconia albicans, however, no information is available about Al-resistance mechanisms in the other species analyzed in the present work. The Al concentration was similar in Miconia lepidota from the shrubland and the forest according to the t-test (p = 0.571), even though the soil Al concentration in the shrubland was higher than that in the forest.…”
Section: Chemical Analysis Of Soils From the Three Plant Formationsmentioning
confidence: 71%